PENGARUH KEPERCAYAAN DAN KOMITMEN TERHADAP LOYALITAS NASABAH BANK BRI UNIT BARAKA - Sandra Sandra, Jayadi, Paramudia (Universitas Diponegoro, 2025)
The problem studied in this research is the service applied to the company, such as the length of service that customers often complain about. Therefore, this research aims: (1) To determine customer trust in Bank BRI Baraka Unit; (2) To determine customer commitment to Bank BRI Baraka Unit; (3) To determine the loyalty of Bank BRI Baraka Unit customers; (4) To determine the effect of customer trust on customer loyalty at BRI Bank Baraka Unit; (5) To determine the effect of customer commitment on customer loyalty at Bank BRI Baraka Unit; and (6) To determine the influence of customer trust and customer commitment on customer loyalty at Bank BRI Baraka Unit. This research was conducted at Bank BRI Baraka Unit. The type of research used in this research is descriptive and associative research. The sampling technique used purposive sampling technique with a total of 100 respondents. The data analysis used is instrument validity and reliability testing, descriptive data analysis, classical assumption testing, inferential statistical analysis and hypothesis testing. The data processing tool uses IBM SPSS version 25. The results of the research showed that the trust of Bank BRI Baraka Unit customers is in the high category, the commitment of Bank BRI Baraka Unit customers is in the high category, the loyalty of Bank BRI Baraka Unit customers is in the consistent category, customer trust has a significant effect on customer loyalty at Bank BRI Unit Baraka, customer commitment has a significant effect on customer loyalty at Bank BRI Unit Baraka, and customer trust and customer commitment have a significant effect on customer loyalty at Bank BRI Unit Baraka.Keywords: Trust; Commitment; Loyalty.